Causal relationship between gut microbiota and differentiated thyroid cancer: a two-sample Mendelian randomization study - Hu, Shaojun; Tang, Chuangang; Wang, Ling; Feng, Fang; Li, Xiaoxin; Sun, Mingyu; Yao, Lijun (Frontiers in Oncology, 2024)
Background: The gut microbiota has been significantly associated with differentiated thyroid cancer (DTC). However, the causal relationship between gut microbiota and DTC remains unexplored. Methods: Genome-wide association studies (GWAS) summary databases were utilized to select exposure and outcome. The Mendelian randomization (MR) method was employed to investigate the causal relationship between gut microbiota and DTC. A sensitivity analysis was performed to assess the reliability of the findings. Results: Four bacterial traits were associated with the risk of DTC: Class Mollicutes (odds ratio [OR] = 10.953, 95% confidence interval [95% CI]: 2.333-51.428, P = 0.002), Phylum Tenericutes (OR = 10.953, 95% CI: 2.333-51.428, P = 0.002), Genus Eggerthella (OR = 3.219, 95% CI: 1.033-10.024, P = 0.044), and Order Rhodospirillales (OR = 2.829, 95% CI: 1.096-7.299, P = 0.032). The large 95% CI range for the Class Mollicutes and the Phylum Tenericutes may be attributed to the small sample size. Additionally, four other bacterial traits were negatively associated with DTC: Genus Eubacterium fissicatena group (OR = 0.381, 95% CI: 0.148-0.979, P = 0.045), Genus Lachnospiraceae UCG008 (OR = 0.317, 95% CI: 0.125-0.801, P = 0.015), Genus Christensenellaceae R-7 group (OR = 0.134, 95% CI: 0.020-0.886, P = 0.037), and Genus Escherichia Shigella (OR = 0.170, 95% CI: 0.037-0.769, P = 0.021). Conclusion: These findings contribute to our understanding of the pathological mechanisms underlying DTC and provide novel insights for the clinical treatment of DTC.